Proces twórczy i sekrety błędów - Dziadek, Adam (Przestrzenie Teorii, 2023)
This text presents a very special creative process, which is an absolute exception in world literature. It is about the formation of My Century by Aleksander Wat and about various types of errors that were revealed during the preparation of the new edition of this work. The errors that appear in previous editions of My Century are of a varied nature. These are primarily “memory errors” of the author himself, there are also errors resulting from faulty listening to the recordings or technical faults in several recordings, and finally errors that are difficult to classify and explain, and which may be associated with exceptional difficulties with establishing the facts.